Modulation of gut microbiota by probiotics to improve the efficacy of immunotherapy in hepatocellular carcinoma - Chen, Ping; Yang, Chengchen; Ren, Ke; Xu, Mingzhi; Pan, Chenwei; Ye, Xuewei; Li, Lanjuan (Frontiers in Immunology, 2024)
Hepatocellular carcinoma, a common malignancy of the digestive system, typically progresses through a sequence of hepatitis, liver fibrosis, cirrhosis and ultimately, tumor. The interaction between gut microbiota, the portal venous system and the biliary tract, referred to as the gut-liver axis, is crucial in understanding the mechanisms that contribute to the progression of hepatocellular carcinoma. Mechanisms implicated include gut dysbiosis, alterations in microbial metabolites and increased intestinal barrier permeability. Imbalances in gut microbiota, or dysbiosis, contributes to hepatocellular carcinoma by producing carcinogenic substances, disrupting the balance of the immune system, altering metabolic processes, and increasing intestinal barrier permeability. Concurrently, accumulating evidence suggests that gut microbiota has the ability to modulate antitumor immune responses and affect the efficacy of cancer immunotherapies. As a new and effective strategy, immunotherapy offers significant potential for managing advanced stages of hepatocellular carcinoma, with immune checkpoint inhibitors achieving significant advancements in improving patients’ survival. Probiotics play a vital role in promoting health and preventing diseases by modulating metabolic processes, inflammation and immune responses. Research indicates that they are instrumental in boosting antitumor immune responses through the modulation of gut microbiota. This review is to explore the relationship between gut microbiota and the emergence of hepatocellular carcinoma, assess the contributions of probiotics to immunotherapy and outline the latest research findings, providing a safer and more cost-effective potential strategy for the prevention and management of hepatocellular carcinoma.